Edaravone Modulates Neuronal GPX4/ACSL4/5-LOX to Promote Recovery After Spinal Cord Injury - Pang, Yilin; Liu, Xinjie; Wang, Xu; Shi, Xuelian; Ma, Lei; Zhang, Yan; Zhou, Tiangang; Zhao, Chenxi; Zhang, Xu; Fan, Baoyou; Hao, Jian; Li, Wenxiang; et al. (Frontiers in Cell and Developmental Biology, 2022)
The FDA-approved drug edaravone has a neuroprotective effect on spinal cord injury (SCI) and many other central nervous system diseases. However, its molecular mechanism remains unclear. Since edaravone is a lipid peroxidation scavenger, we hypothesize that edaravone exerts its neuroprotective effect by inhibiting ferroptosis in SCI. Edaravone treatment after SCI upregulates glutathione peroxidase 4 (GPX4) and system Xc-light chain (xCT), which are anti-ferroptosis proteins. It downregulates pro-ferroptosis proteins Acyl-CoA synthetase long-chain family member 4 (ACSL4) and 5-lipoxygenase (5-LOX). The most significant changes in edaravone treatment occur in the acute phase, two days post injury. Edaravone modulates neuronal GPX4/ACSL4/5-LOX in the spinal segment below the lesion, which is critical for maintaining locomotion. Moreover, the GPX4/ACSL4/5-LOX in motor neuron is also modulated by edaravone in the spinal cord. Therefore, secondary injury below the lesion site is reversed by edaravone via ferroptosis inhibition. The cytokine array revealed that edaravone upregulated some anti-inflammatory cytokines such as IL-10, IL-13, and adiponectin. Edaravone reduced microgliosis and astrogliosis, indicating reduced neuroinflammation. Edaravone has a long-term effect on neuronal survival, spinal cord tissue sparing, and motor function recovery. In summary, we revealed a novel mechanism of edaravone in inhibiting neuronal ferroptosis in SCI. This mechanism may be generalizable to other neurological diseases.